Ազգերի կերպարները միջնադարյան արաբալեզու աղբյուրներում (IX-XI դդ.) - Միքայելյան, Տիգրան («Զանգակ - 97»)
The article presents images and stereotypes of different peoples and inhabitants of various provinces of the Arab Caliphate as seen by medieval Arab Muslim authors such as Ibn al-Fakih (IX c), al-Muqaddasi (X c) and others. The articles also discusses images of women belonging to different peoples. their attractive and negative features in a guide for purchasing slaves of Ibn Butlan, a Baghdadi physician (XI c.). These images and stereotypes, also being subjective and egocentric, enable us to see some aspects of Aräbo-Muslim medieval society's aesthetic views and world oudook.
Keywords: Ազգագրություն; Պատմություն